Relapse Rate and Clinical Risk Factors Affecting the Treatment of Graves’ Disease - Kiatpanabhikul, Phatharaporn (Siriraj Medical Journal, 2021)
Objective: To determine the relapse rate of Graves’ disease (GD) and identify important clinical risk factors for relapse. Materials and Methods: This was a 10-year retrospective cohort study. Information was collected with ICD10 E050 codes for Graves’ hyperthyroidism among Thai patients of both sexes and all ages with no history of pregnancy, thyroid storm or antithyroid drug (ATD) allergy. Results: The 286 included GD patients had a relapse rate of 35% after ATD withdrawal for one year. The clinical risk factors associated with relapse were male sex (p = 0.014), smoking (p = 0.001), serum free T4 (FT4) levels > 2 times the upper normal range at diagnosis (p = 0.005), duration for maintenance treatment < 6 and 9 months (p < 0.005) compared with remission. A TSH level < 1 mIU/L (p = 0.060) and MMI > 2.5 mg per day before ATD withdrawal (p = 0.094) trended toward associations with relapse. The clinical factors that predicted GD relapse were serum FT4 levels at diagnosis (p = 0.006) and serum free T3 (FT3) levels before ATD withdrawal (p = 0.019). Conclusion: Male sex, smoking and serum FT4 levels at diagnosis > 2 times the normal range were significant clinical factors for GD relapse in Thai patients. To reduce the relapse rate in the first year, MMI should be used in maintenance periods for 9 to 12 months with serum FT3 levels within low-normal ranges before ATD withdrawal. This would promote future guidelines for GD management in Thailand.